BASIC CHARACTERISTICS OF TRANSLATING LITERARY TEXTS - Maftunakhon Abduolimova; Tolipova Gullola (Galaxy International Interdisciplinary Research Journal, 2024)
This article describes the translation of the spiritual heritage of the nation, which is a cultural bridge between nations, the elements that need to be taken into account in the translation process, types of translation, literary translation, and the correct translation of phraseology in the translation process.